2021
DOI: 10.1371/journal.pone.0249635
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory and pre-planned actions: A comparison between young soccer players and swimmers

Abstract: The present study investigated whether a difference exists in reactive and proactive control for sport considered open or closed skills dominated. Sixteen young (11–12 years) athletes (eight soccer players and eight swimmers) were asked to be engaged into two games competitions that required either a reactive and a proactive type of control. By means of kinematic (i.e. movement time and duration) and dynamic analysis through the force platform (i.e. Anticipatory Postural Adjustments, APAs), we evaluated the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Certainly, the artistic gymnastics facilitates abilities, such as the estimation of the direction of movements, the speed of execution, and the identification of their own and surrounding objects' locations [44] , but these considerations cannot be sufficient to definitely answer the question. Other studies using the table-RAM should be performed on other young people playing sports, for example considering open skill sport, that take place in an unpredictable and constantly changing environment where movements need to be continually adapted, such as basketball, soccer [45] . In addition to this question, it is necessary to underline the limitations of the present study which cannot be overcome requiring caution when generalize the data.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, the artistic gymnastics facilitates abilities, such as the estimation of the direction of movements, the speed of execution, and the identification of their own and surrounding objects' locations [44] , but these considerations cannot be sufficient to definitely answer the question. Other studies using the table-RAM should be performed on other young people playing sports, for example considering open skill sport, that take place in an unpredictable and constantly changing environment where movements need to be continually adapted, such as basketball, soccer [45] . In addition to this question, it is necessary to underline the limitations of the present study which cannot be overcome requiring caution when generalize the data.…”
Section: Discussionmentioning
confidence: 99%
“…Although the literature presents a variety of protocols for using IMUs in sports [ 3 , 5 , 23 ], is important to recognize that this area of research is still under development, especially when we look for evidence supporting the use of wearable sensors to assess CPAs and APAs during a predictable external perturbation in a real sport setting. The difficulty in studying APAs in this environment is one of the reasons why the literature is scarce.…”
Section: Discussion and Implicationmentioning
confidence: 99%
“…Some practical application may derive from these results, since no matter the type of sport, they all highlight the need for athe daptability and reorganization of posture adjustments to maintain balance, lower the risk of injuries, and improve performance. APAs are useful to detect and train position-specific patterns in movement; create more efficient sports-specific training programs for performance optimization; and monitor potential risks of injury, such as concussion and fatigue [ 3 , 23 ].…”
Section: Discussion and Implicationmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it has been reported that the development of anticipatory postural control with voluntary movement while standing is influenced by experience as well as by the development of the nervous system, resulting in significant individual differences [ 23 ]. Thus, the training effect of anticipatory postural control from childhood to adolescence has been investigated with respect to sports [ 24 ] and rehabilitation [ 25 , 26 ]. However, previous studies have reported the development of anticipatory activation of the postural muscles with arm movement during standing based on typical examples or average data from a few subjects [ 19 , 22 ].…”
Section: Introductionmentioning
confidence: 99%